Effectiveness of Back care education Programme among school children: a systematic review of randomized controlled trials - Canice Chukwudi Anyachukwu; Confidence Chinemerem Amarah; Blessing Chiagozikam Atueyi; Ifeanyi Anthony; Martins Nweke; Ukachukwu Abaraogu (BMC Pediatrics, 2024)
Abstract Study design Systematic review of Randomised controlled trials. Objectives With the increasing incidence of back pain among children and its untold implications to their future, back education tailored in an effective way would be indicated. However literature appears unsettled. This study aims to review available literature to determine the effect of school-based back education in preventing and managing low back pain in school children. Methods Randomized controlled trials carried out on elementary and secondary school children of ages 6 to 18 years and published in English language were included. Back education taught in hospitals or other settings were excluded. Primary outcome was back pain prevalence and secondary outcomes were constituted from the study characteristics of selected studies which includes: back behavior, knowledge, postural habits, physical activity, fear-avoidance beliefs, back pack carriage, pain intensity, skills and self efficacy. Databases searched were PEDro, HINARI, PubMed, Cochrane, and Google Scholar. Available stiudies from 2000 to March 2022 were retrieved. Quality of studies were assessed using the PEDro scale. Obtained studies were descriptively analyzed. Results A total 8420 studies were retrieved and 8 studies (with 1239 participants) were included in this review. Four studies each assessed back knowledge and back behavior, and two assessed back pain prevalence. There were improvements in back knowledge and back behaviour, but effectiveness of back care education on back pain prevalence was not conclusive. Forms of education used involved the indirect method of conditioning the environment and the direct method which made use of theory, practical lessons and educational books and materials. Conclusion Back care education programmes in schools are effective in improving back care knowledge, behavior and reduction in low back pain frequency. Reduction in back pain prevalence is not conclusive. Back care education could be incorporated as part of schools’ education programmes. Limitations include exclusion of non English language studies and inconsistent outcome measures. Funding source None. Registration This review protocol was registered under the International platform of Registered systematic review and meta-analysis protocol (INPLASY) with the registration number; INPLASY202310044 and DOI number; https://doi.org/10.37766/inplasy2023.1.0044